Ceramic slurry, ceramic diaphragm and ion rechargeable battery
By using porous cordierite ceramic powder to prepare ceramic slurry, the problem of low ionic conductivity of the existing ceramic coating layer is solved, and a ceramic separator with high ionic conductivity and good thermal stability is achieved, which improves the rate performance and energy density of the battery.
Patent Information
- Application Number
- CN202411889636.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-21
AI Technical Summary
The existing ceramic coating lacks effective ionic conductivity, resulting in low ionic conductivity, limiting its application in high-performance sodium and lithium-ion batteries.
The ceramic slurry is prepared by porous cordierite ceramic powder, and through its unique hexagonal crystal structure and complex three-dimensional network, a ceramic diaphragm with high ionic conductivity and good thermal stability is formed.
It significantly improves the ionic conductivity and thermal stability of the ceramic separator, enhances the rate performance and energy density of the battery, and reduces the thermal expansion coefficient and improves the sustainability of the material.
Smart Images

Figure CN119674441A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion battery materials, and in particular to a ceramic slurry, a ceramic diaphragm and an ion rechargeable battery. Background Art
[0002] Battery separators are a vital component of ion rechargeable batteries. Their good ionic conductivity allows sodium and lithium ions to pass through during the charge and discharge process while preventing the flow of electrons, thereby maintaining the battery's chemical reactions and current conduction. The separator effectively separates the positive and negative electrodes to prevent the two electrodes from directly contacting each other and causing a short circuit. This feature is critical to ensuring battery safety. Separator materials usually have a certain degree of thermal stability and can maintain their structural integrity within a certain temperature range, thereby reducing the risk of thermal runaway caused by overheating. The separator provides the necessary mechanical support to ensure that the material will not break or peel off due to volume changes during the charge and discharge process, thereby improving the cycle life and reliability of the battery. Although separators play an important role in lithium-ion batteries, they still face several challenges. With the development of high energy density and fast charge and discharge technology, the performance requirements for separator materials continue to increase, including higher ion conductivity, lower electronic conductivity and better temperature resistance.
[0003] At present, boehmite is commonly used as a ceramic coating layer in the preparation of ceramic diaphragms. However, due to its compact crystal structure, high migration energy barrier, and lack of effective ion conduction channels, its ion conductivity is relatively low. These characteristics limit its widespread use in high-performance sodium and lithium-ion batteries and other applications.
[0004] In view of this, this patent application is filed. Summary of the invention
[0005] In order to solve the technical problem that the current ceramic coating layer has low ion conductivity due to the lack of effective ion conduction channels, the present invention provides a ceramic slurry, a ceramic diaphragm using the ceramic slurry as a coating layer, and a sodium and lithium ion battery.
[0006] The present invention is achieved through the following technical solutions:
[0007] The first object of the present invention is to provide a ceramic slurry, comprising the following components in parts by weight: 12-58.8 parts of ceramic powder, 0.1-10 parts of binder, 0.1-5 parts of dispersant, 0.01 parts to 2 parts of thickener, and 40-80 parts of water;
[0008] The ceramic powder is any one of cordierite ceramic powder, aluminosilicate system ceramics, and magnesium aluminum spinel powder, or a mixture of several of them.
[0009] Cordierite (2MgO.2Al 2 O3 .5SiO 2 ) There are three common allotropes of crystals, namely μ-cordierite, β-cordierite and α-cordierite. Among them, μ-cordierite belongs to the monoclinic system. β-cordierite belongs to the orthorhombic system, and α-cordierite is a high-temperature type of cordierite, also known as Indian stone, which belongs to the hexagonal system. The main component of the cordierite ceramic described in this patent is α-cordierite with a hexagonal crystal structure, and its crystal contains tetrahedral and octahedral units of magnesium, aluminum and silicon, forming a complex three-dimensional network. This structure allows ions to move freely in its lattice, especially lithium ions and sodium ions, with a low migration energy barrier and strong ionic conductivity; and α-cordierite has the lowest thermal expansion coefficient among the three allotropes, has good thermal stability, and combines excellent properties such as high strength, high porosity, and low thermal expansion coefficient. Therefore, this patent selects porous cordierite ceramics to prepare ceramic diaphragms, which can increase the thermal stability and ionic conductivity of the diaphragm. The relative density of cordierite is about 2.6. Cordierite ceramics are porous materials with lower relative density. It is beneficial to use them in high-rate batteries to improve their energy density. In addition to good performance, this material also has the characteristics of sustainable development.
[0010] As a preferred solution, the cordierite ceramic powder has a D 50 The particle size of cordierite ceramic powder is 0.5-2.5μm. As the particle size of cordierite ceramic powder gradually increases, the packing density of cordierite ceramic powder decreases, and the number of cordierite ceramic particles per unit area of the base film decreases, resulting in less contact between the base film and the cordierite ceramic particles, making it impossible to effectively prevent the shrinkage of the base layer.
[0011] As a preferred solution, the binder is any one of polyvinylidene fluoride, polyvinyl alcohol, polyvinyl acetate, styrene-butadiene latex, styrene-acrylic latex or polyacrylic acid, or a mixture of several thereof. As a preferred solution, the dispersant is any one of sodium carboxymethyl cellulose, sodium polyacrylate, ammonium polyacrylate, carboxylates and sulfonates, or a mixture of several thereof.
[0012] As a preferred solution, the thickener is one or a mixture of polyacrylamide, polyethylene oxide, polyacrylonitrile or polyurethane.
[0013] The second object of the present invention is to provide a ceramic diaphragm, the preparation material of which includes the ceramic slurry as described in any one of the above items.
[0014] The third object of the present invention is to provide a method for preparing a ceramic diaphragm, comprising the following steps:
[0015] Preparation of ceramic slurry: Mix the raw materials according to the ratio, first mix the ceramic powder, water and dispersant, then add the binder and thickener, and stir;
[0016] Coating: The ceramic slurry is coated on the base film, and then baked and dried to obtain a ceramic coated diaphragm.
[0017] As a preferred solution, when preparing the ceramic slurry, ceramic powder, water and dispersant are mixed, stirred at 800-10000 r / min for 20-60 min, and after adding the binder and thickener, stirred at 800-10000 r / min for 30-90 min;
[0018] During coating, the ceramic coating is baked at 35°C-90°C for 1-20 minutes.
[0019] As a preferred solution, the base film is any one of a polyethylene microporous film, a polypropylene microporous film, and a polyethylene and polypropylene composite microporous film;
[0020] And / or, the base film has a thickness of 5-30 μm;
[0021] and / or, the porosity of the base film is 30-70%;
[0022] And / or, the thickness of the ceramic coating is 0.5-4 μm;
[0023] And / or, the ceramic slurry is coated on one side or both sides of the base film.
[0024] A fourth object of the present invention is to provide an ion rechargeable battery, which is a sodium ion battery or a lithium ion battery, comprising the ceramic diaphragm as described in any one of the above items.
[0025] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0026] The ceramic slurry provided by the present invention uses cordierite ceramic powder as the main raw material, has a layered crystal structure, and forms a hexagonal crystal structure. The crystal contains tetrahedral and octahedral units of magnesium, aluminum and silicon, forming a complex three-dimensional network. This structure allows ions to move freely in its lattice, especially lithium ions and sodium ions, and the migration energy barrier is low, so that the cordierite ceramic powder of the present invention has high ionic conductivity. The relative density of cordierite is about 2.6, and cordierite ceramics are porous materials with lower relative density. The use of high-rate batteries significantly improves their energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:
[0028] Figure 1 The discharge curves of the soft-pack batteries prepared by the ceramic diaphragms of Example 2 and the comparative example at a 10C rate. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0030] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0031] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0032] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0033] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0034] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0035] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0036] Embodiment 1:
[0037] A production process for a lithium battery separator is carried out according to the following steps:
[0038] 1) Ceramic slurry preparation: 3 kg of cordierite powder with a particle size of 1.0-1.5 μm, 7.5 kg of deionized water and 0.3 kg of sodium carboxymethyl cellulose were mixed and stirred at high speed for 30 minutes at 5000 r / min; then 1.5 kg of polyvinylidene fluoride and 0.2 kg of polyacrylamide were added and stirred at 5000 r / min for 30 minutes to obtain ceramic slurry;
[0039] 2) Coating: The ceramic slurry prepared in step 1) is coated on one side of a polyethylene microporous membrane with a thickness of 10 μm, and baked at a temperature of 40°C-85°C for 10 minutes to obtain a ceramic coating to prepare a lithium battery ceramic diaphragm, wherein the thickness of the ceramic coating is about 3 μm.
[0040] Embodiment 2:
[0041] 1) Ceramic slurry preparation: 5 kg of cordierite ceramic powder with a particle size of 1.0-1.5 μm, 6.8 kg of deionized water and 0.1 kg of sodium carboxymethyl cellulose were mixed and stirred at high speed for 30 minutes at 5000 r / min; then 0.8 kg of polyvinyl alcohol and 0.1 kg of polyethylene oxide were added and stirred at 5000 r / min for 30 minutes to obtain cordierite ceramic slurry;
[0042] 2) Coating: The cordierite ceramic slurry obtained in step 1) is coated on one side of a polyethylene microporous membrane with a thickness of 20 μm, and baked at a temperature of 40°C-85°C for 10 minutes to obtain a ceramic coating to obtain a lithium battery ceramic separator, wherein the thickness of the ceramic coating is about 4 μm and the porosity of the polyethylene microporous membrane is 50%.
[0043] Example 3
[0044] 1) Ceramic slurry preparation: 5 kg of cordierite powder with a particle size of 1.0-1.5 μm, 7.5 kg of deionized water and 0.03 kg of ammonium polyacrylate were mixed and stirred at high speed for 30 minutes at 5000 r / min; then 1.5 kg of polyvinylidene fluoride and 0.2 kg of polyacrylamide were added and stirred at 5000 r / min for 30 minutes to obtain ceramic slurry;
[0045] 2) Coating: The ceramic slurry prepared in step 1) is coated on one side of a polyethylene microporous membrane with a thickness of 20 μm, and baked at a temperature of 40°C-85°C for 10 minutes to obtain a cordierite ceramic coated diaphragm, wherein the thickness of the ceramic coating is about 4 μm.
[0046] Embodiment 4:
[0047] The difference from Example 3 is that the particle size of the cordierite ceramic powder is replaced with 0.5-1.0 μm, and the rest is the same as Example 3.
[0048] Embodiment 5:
[0049] The difference from Example 3 is that the particle size of the cordierite ceramic powder is replaced with 1.5-2.0 μm, and the rest is the same as Example 3.
[0050] Embodiment 6:
[0051] The difference from Example 3 is that the particle size of the cordierite ceramic powder is replaced with 2.0-2.5 μm, and the rest is the same as Example 3.
[0052] Comparative Example 1:
[0053] 1) Ceramic slurry preparation: 5 kg of boehmite powder with a particle size of 1.0-1.5 μm, 6.8 kg of deionized water and 0.1 kg of sodium carboxymethyl cellulose were mixed and stirred at high speed for 30 minutes at 5000 r / min; then 0.8 kg of polyvinyl alcohol and 0.1 kg of polyethylene oxide were added and stirred at 5000 r / min for 30 minutes to obtain boehmite ceramic slurry;
[0054] 2) Coating: The boehmite ceramic slurry obtained in step 1) is coated on one side of a polyethylene microporous membrane with a thickness of 20 μm, and a ceramic coating is obtained after baking at a temperature of 40°C-85°C for 10 minutes to obtain two lithium battery ceramic separators, wherein the thickness of the ceramic coating is about 4 μm and the porosity of the polyethylene microporous membrane is 50%.
[0055] Test 1:
[0056] Using the diaphragms prepared in Example 1 and Comparative Example 1, three samples were cut into a size of 200 mm×200 mm, and performance tests were performed on them. The test results are shown in Table 1.
[0057] Table 1 Diaphragm performance test results
[0058]
[0059] As can be seen from Table 1, the ceramic diaphragm made of cordierite ceramic as a coating has a small thermal shrinkage rate, which is due to the low thermal expansion coefficient and fine grain structure of cordierite ceramic, which makes cordierite ceramic have good thermal insulation performance. However, the ceramic diaphragm obtained by using boehmite ceramic in Comparative Example 1 has a large shrinkage rate. In terms of tensile strength, the diaphragms of Example 1 and Comparative Example 1 are not much different.
[0060] Test 2:
[0061] The diaphragms prepared by the methods of Example 2 and Comparative Example 1 were stacked with lithium cobalt oxide positive electrode sheets and graphite negative electrode sheets to form soft-package lithium-ion batteries. The prepared lithium batteries were then subjected to charge and discharge and 10C rate performance tests. The test results are shown in Tables 2 and 3. Figure 1 shown.
[0062] Table 2 Comparison of energy density of soft pack batteries
[0063] Example 2 Comparative Example 1 Energy density (Wh / kg) 240 232
[0064] As shown in Table 2, low-density, high-ion-conductivity cordierite ceramics as ceramic coatings for separators can effectively increase the energy density of batteries. Under the same conditions, the energy density is greatly increased from 232Wh / kg in Comparative Example 1 to 240Wh / kg, which is a major breakthrough in the field of lithium-ion batteries. Figure 1It can be seen that the capacity retention rate of the soft-pack battery made of the cordierite ceramic separator in Example 2 is better than that of the soft-pack battery made of boehmite ceramic in Comparative Example 1 in 10C rate discharge. This is due to the higher ionic conductivity of the cordierite ceramic separator.
[0065] Comparative Example 2:
[0066] The difference from Example 3 is that the particle size of the cordierite ceramic powder is replaced with 2.5-3.0 μm, and the rest is the same as Example 3.
[0067] Test 3:
[0068] The diaphragms prepared in Examples 3 to 6 and Comparative Example 2 were used to cut samples into a size of 200 mm×200 mm, and performance tests were performed on them. The test results are shown in Table 3.
[0069] Table 3 Performance of ceramic coated diaphragms containing different particle sizes of cordierite
[0070]
[0071] From the data in Table 3, it can be seen that as the particle size of cordierite ceramics gradually increases, the air permeability does not change significantly, but the thermal shrinkage has a significant increasing trend. This is because as the particle size gradually increases, the packing density of cordierite ceramics decreases, and the number of cordierite ceramics per unit area of the PE base film decreases, resulting in less contact between the PE base film and the cordierite ceramic particles, which cannot effectively prevent the shrinkage of the base layer. Thermal shrinkage performance is one of the important indicators of coated diaphragms. Excellent performance coated diaphragms require good air permeability and low thermal shrinkage, so the final cordierite ceramic particle size is selected to be 0.5-2.5μm.
[0072] In summary, the ceramic slurry and ceramic diaphragm of the present invention have the following advantages:
[0073] 1. The slurry in the present invention uses cordierite ceramic as the main material, which belongs to the hexagonal crystal system. It has unique open channels, highly symmetrical structures, low migration energy barriers and possible doping effects, which enable it to exhibit excellent ionic conductivity and can effectively improve its rate performance when used in batteries.
[0074] 2. The cordierite ceramics in the present invention have the advantage of being lightweight. Compared with commonly used silicon oxide and zirconium oxide, their relative density is about 2.6. In addition, the cordierite ceramics are porous materials with lower relative density. The ceramic diaphragms prepared from such lightweight materials are used in high-rate batteries to significantly improve their energy density.
[0075] The above specific implementation methods further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific implementation methods of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A ceramic slurry, characterized in that: The invention comprises the following components in parts by weight: 12-58.8 parts of ceramic powder, 0.1-10 parts of adhesive, 0.1-5 parts of dispersant, 0.01-2 parts of thickener, and 40-80 parts of water; The ceramic powder is any one of cordierite ceramic powder, aluminosilicate system ceramics, and magnesium aluminum spinel powder, or a mixture of several of them.
2. A ceramic slurry according to claim 1, characterized in that: The cordierite ceramic powder has a D 50 0.5-2.5μm.
3. A ceramic slurry according to claim 1, characterized in that: The binder is any one of polyvinylidene fluoride, polyvinyl alcohol, polyvinyl acetate, styrene-butadiene latex, styrene-acrylic latex or polyacrylic acid, or a mixture of several of them.
4. The ceramic slurry according to claim 1, characterized in that: The dispersant is any one of sodium carboxymethyl cellulose, sodium polyacrylate, ammonium polyacrylate, carboxylates and sulfonates, or a mixture of several of them.
5. The ceramic slurry according to claim 1, characterized in that: The thickener is one or a mixture of polyacrylamide, polyethylene oxide, polyacrylonitrile or polyurethane.
6. A ceramic diaphragm, characterized in that: The preparation material thereof includes the ceramic slurry as described in any one of claims 1 to 5.
7. The method for preparing a ceramic diaphragm according to claim 6, characterized in that: The following steps are involved: Preparation of ceramic slurry: Mix the raw materials according to the ratio, first mix the ceramic powder, water and dispersant, then add the binder and thickener, and stir; Coating: Coat the ceramic slurry on the base film, bake and dry it to obtain a ceramic coated diaphragm.
8. The method for preparing a ceramic diaphragm according to claim 6, characterized in that: When preparing the ceramic slurry, ceramic powder, water and dispersant are mixed, stirred at 800-10000 r / min for 20-60 min, and after adding the binder and thickener, stirred at 800-10000 r / min for 30-90 min; The ceramic coated diaphragm is baked at 35°C-90°C for 1-20 minutes.
9. The method for preparing a ceramic diaphragm according to any one of claims 6 to 8, characterized in that: The base film is any one of a polyethylene microporous film, a polypropylene microporous film, and a polyethylene and polypropylene composite microporous film; And / or, the base film has a thickness of 5-30 μm; and / or, the porosity of the base film is 30-70%; And / or, the thickness of the ceramic coating is 0.5-4 μm; And / or, the ceramic slurry is coated on one side or both sides of the base film.
10. An ion rechargeable battery, wherein the ion rechargeable battery is a sodium ion battery or a lithium ion battery, characterized in that: It comprises the ceramic diaphragm as described in any one of claims 6 to 9.
Citation Information
Cited By
A high rate ceramic-coated separator
CN122659497A